Analisis Kebijakan dan Program Pendidikan Masyarakat pada Pusat Kegiatan Belajar Masyarakat ( PKBM) - Lulu Yuliani (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2017)
Abstract: Community Learning Center is a non-formal educational institution that aims to serve the community. Services CLC in meeting the educational needs is very important, especially for people in need. Basically the goal of CLC presence in a community is to realize an improved quality of life of the community in the broadest sense. An understanding of the quality of life of a community is determined by the values of life and believed by the community. CLC (community based education) is the actualization characterized the (1) the support of the community in various forms; (2) community involvement in decision-making; (3) a partnership in which citizens participate in a relationship that is aligned with program managers; (4) ownership in which citizens participate in control of all decisions related to educational programs outside of school. CLC is the quality and quantity of public participation in the planning, establishment, implementation, and development. Keywords: Policy, Public Education, Community Learning Center